Philosophy as politics of emancipation: tracing Marx and Badiou - Koljević, Bogdana (Sociološki pregled, 2020)
Beginning, first and foremost, from Marx’s and Badiou’s analyses, the concept of philosophy as politics of emancipation is considered. Politics of power via politics of force and violence is contrasted to a contemporary line of rethinking politics of emancipation and the emphasis – besides the exploration of practices of freedom, justice and equality – is placed on Marx’s idea of „true democracy” (wahre Demokratie). This refers to rethinking politics of the people and reflecting the issue about the engaged structure of knowledge which precisely as emancipatory knowledge turns out to be decisive for political action, resistance and the foundation of a democratic state. With the rebirth of history, the potentials for confronting neoliberalism as “capitalo-parliamentarism” are reopened, as well as the potentials for the construction of democracy as the rule of the people. The basis of contemporary political ontology appears in the relation between politics of the people and the politics of truth.
Keywords: politics of emancipation; freedom; equality; truth; the people